Partial Use of Cushuro Flour and Refined Anchovy Oil for the Technological Preparation of Cookies - Carlos-Puma, Karlos; Alvites-Ruesta, Walter; Villalobos-Meneses, Bertha; Huamani-Palomino, Wilmer; Rua-Pomahuacre, Silvia; Zevallos-Vera, Erika; Vallejos-Zuta, Alex (LACCEI, 2025)
Nowadays, different diseases caused by poor diet have been detected, one of the most worrying in our country is anemia. Of which, its annual rates have not registered improvements compared to previous years, representing a worrying issue for the Peruvian government and which puts public health on alert. The present research proposes the preparation of cookies in which conventional flour is replaced with a percentage of Cushuro flour and refined anchovy oil, offering great nutritional value. For this purpose, three formulations composed of these ingredients were tested, subjecting them to physicochemical and microbiological analysis, comparing the values obtained with the quality and safety standard of permissible limits, then carrying out the sensory evaluation of cookies to determine the level of acceptability of each type of formulation through the Turkey Test and ANOVA. Obtaining as the winning formulation, Formulation I.